Agricultural industrial scale, price random fluctuation, and profitability levels: evidence from China’s pig industry - Yang, Qing; Qiao, Shiyan; Ying, Ruiyao (Frontiers in Sustainable Food Systems, 2024)
Introduction Promoting the development of large-scale pig farming is a crucial measure implemented by the Chinese government to regulate the pig market. Methods By utilizing panel data from 30 provinces in China spanning from 2003 to 2020 and employing the PVAR model, this study examines the relationships among price random fluctuations, profftability levels, and industrial scale. Results and discussion The findings reveal that industrial scale can effectively mitigate price random fluctuations; however, it also leads to a decrease in relative hog prices. Moreover, there exists significant heterogeneity in the impact of scaling on price random fluctuations. Increasing the proportion of farmers engaged in pig farming with a scale ranging from 500 to 9,999 heads reduces random price fluctuations, while increasing the proportion of farmers involved in pig farming with a scale exceeding 10,000 heads has no effect on stabilizing such fluctuations. Additionally, threshold effects are observed for epidemics and environmental regulations. When environmental regulations are less stringent, industrial scale enhances relative prices and stabilizes random fluctuations; nevertheless, once certain thresholds are surpassed, industrial scale diminishes relative prices and eliminates its stabilizing effect on random fluctuations. Similarly, after an epidemic surpasses its threshold level, industry scale fails to stabilize random price fluctuations. These findings provide valuable insights for governments when formulating industrial policies aimed at mitigating agricultural market risks.